Description of Yellowfin Tuna Processing - Akerina, Febrina Olivia; Kour, Femsy; Radja, Christiani Melitia; Pesondolang, Loisa Vebiola (Jurnal Ilmiah Platax, 2024)
Morotai Island Regency has very abundant potential, namely tuna. The abundance of tuna fishermen's catches has become an opportunity to develop tuna loin processing, one of which is at PT. Harta Samudra Morotai. This research aims to describe the processing process carried out at PT. Harta Samudra. PT. Harta Samudra has 90 employees, 84 of whom are residents. Of the total employees, 11 are permanent employees and the other 79 are daily employees. The tuna loin processing process refers to SNI 01-4104.3-2006: receiving, beheading, butchering, trimming, gas room, chiller, retouching, packing, stuffing, and laboratory analysis. Keywords: Yellowfin Tuna; Frozen Loin Tuna; PT. Harta Samudra Abstrak Kabupaten Pulau Morotai, memiliki potensi yang sangat melimpah, yakni tuna. Melimpahnya hasil tangkapan nelayan tuna, menjadi peluang dikembangkannya pengolahan Tuna loin salah satunya di PT. Harta Samudra Morotai. Penelitian ini bertujuan untuk mendeskripsikan proses pengolahan yang dilakukan di PT. Harta Samudra. PT. Harta samudra memiliki 90 karyawan, 84 diantaranya merupakan penduduk lokal. Dari total keseluruhan karyawan 11 diantaranya merupakan karyawan tetap dan 79 lainnya merupakan karyawan harian. Proses pengolahan tuna loin mengacu pada SNI 01-4104.3-2006 yakni receiving, deheading, butchering, trimming, gas room, chiller, retouching, packing, stuffing dan analisis laboratorium. Kata Kunci : Tuna Ekor Kuning; Tuna Loin Beku; PT. Harta Samudra